Angiotensin receptor-neprilysin inhibitor improves coronary collateral perfusion - Li, Kangbo; Kratzmann, Victoria; Dai, Mengjun; Gatzke, Nora; Rocic, Petra; Bramlage, Peter; Grisk, Olaf; Lubomirov, Lubomir T.; Hoffmeister, Meike; Lauxmann, Martin A.; Ritter, Oliver; Buschmann, Eva; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background We investigated the pleiotropic effects of an angiotensin receptor-neprilysin inhibitor (ARNi) on collateral-dependent myocardial perfusion in a rat model of coronary arteriogenesis, and performed comprehensive analyses to uncover the underlying molecular mechanisms. Methods A rat model of coronary arteriogenesis was established by implanting an inflatable occluder on the left anterior descending coronary artery followed by a 7-day repetitive occlusion procedure (ROP). Coronary collateral perfusion was measured by using a myocardial particle infusion technique. The putative ARNi-induced pro-arteriogenic effects were further investigated and compared with an angiotensin-converting enzyme inhibitor (ACEi). Expression of the membrane receptors and key enzymes in the natriuretic peptide system (NPS), renin-angiotensin-aldosterone system (RAAS) and kallikrein-kinin system (KKS) were analyzed by quantitative polymerase chain reaction (qPCR) and immunoblot assay, respectively. Protein levels of pro-arteriogenic cytokines were measured by enzyme-linked immunosorbent assay, and mitochondrial DNA copy number was assessed by qPCR due to their roles in arteriogenesis. Furthermore, murine heart endothelial cells (MHEC5-T) were treated with a neprilysin inhibitor (NEPi) alone, or in combination with bradykinin receptor antagonists. MHEC5-T proliferation was analyzed by colorimetric assay. Results The in vivo study showed that ARNis markedly improved coronary collateral perfusion, regulated the gene expression of KKS, and increased the concentrations of relevant pro-arteriogenic cytokines. The in vitro study demonstrated that NEPis significantly promoted MHEC5-T proliferation, which was diminished by bradykinin receptor antagonists. Conclusion ARNis improve coronary collateral perfusion and exert pro-arteriogenic effects via the bradykinin receptor signaling pathway.